Closing the gap: closure cost estimation trends and pathways to improved maturity - Sanders, J; Slingerland, N; Murphy, D (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
In an ideal scenario, the upper and lower confidence limits of a closure cost estimate should align with the base estimate as mine closure planning progresses; however, this is rarely the case. As mines approach closure, cost estimates typically rise. Despite various approaches proposed to improve cost estimate accuracy over the years, cost overruns remain common. The authors suggest that the issue lies not only in the estimation approaches but also in the misalignment between the maturity of closure planning and the level of cost estimate accuracy required. Current estimating tools and approaches are not flawed; instead, robust closure planning and design are often inadequately applied. The paper suggests actions to improve closure design maturity at each stage of the mine life, ensuring cost estimate inputs mature appropriately as the closure date approaches. Examples and case studies highlight the common disconnect between closure maturity and cost estimate accuracy. A review of closure cost estimation tools and approaches over the past 20 years shows that cost overruns are widespread, indicating that estimation approaches might not be the sole issue. With growing scrutiny on closure-related environmental, social and governance commitments, the mining industry needs to produce more confident, accurate and transparent closure cost estimates. This paper underlines existing and practical methods for improving estimation inputs.
Keywords: closure cost estimation; closure planning; closure maturity; case study